Protest Potential of Regional Students in Russia: Social Prerequisites - Inna S. Shapovalova; Irina N. Valieva (National Research Mordova State University, 2022)
Introduction. The protest potential of youth is a complex, integrative concept that allows one to assess the existing prerequisites for the emergence of protest tension, protest readiness and protest activity of the subject. The scientific problem facing the industry community is establishing continuity between these indicators and predicting possible incidents in the youth environment, as well as significant behavioral reactions to social risks of the environment. Materials and Methods. The article proposes the results and analysis of materials from a 2021 study conducted among student youth in the Russian region (Belgorod Oblast) using a combined survey method (online survey and tablet interviews), using a spontaneous sample, in which quantitative limits were laid for the participation of respondents from different educational institutions, directions of training and courses. On the basis of the developed online form, 1557 respondents, aged 18 to 24, who study at regional universities, were interviewed. Results. On the basis of the proposed typology of protest potential, the regional protest potential of student youth is defined as a "progressive" type - a ripening protest mood, which has a particularly well-grounded discontent and readiness for its manifestation. The regional prerequisites for the formation of protest tension based on the reflection of the social situation, assessment of social security, diagnostics of violation of constitutional rights and freedoms, as well as discrimination of young people in the areas of receiving social services have been determined. Revealed the protest readiness not only to permitted, but also to prohibited forms of protest, determined the indices of the likelihood of the implementation of protest practices by student youth in the region. The protest activity of student youth was assessed as insignificant in the field of illegitimate forms of protest. Discussion and Conclusion. The data obtained make it possible to clarify a number of provisions related to the political activity of young people, to supplement the scientific basis on this issue of sectoral sociologies (youth sociology, political sociology), to actualize the scientific problem of finding and developing methodological tools for measuring the prerequisites of protest potential, creating mathematical models for predicting youth protest activity. Research materials have been and can be in demand by governing bodies of state youth policy of different levels, state and municipal governing bodies, governing bodies of the Ministry of Internal Affairs, youth organizations, and educational institutions.